2007
DOI: 10.1021/es070850f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Removal via Nitrite from Municipal Wastewater at Low Temperatures using Real-Time Control to Optimize Nitrifying Communities

Abstract: Although many studies regarding nitrogen removal via nitrite have been carried out, very limited research has been undertaken on nitrogen removal via nitrite at low temperatures. In this study, to improve the nitrogen removal efficiency from municipal wastewater, a pilot-plant of sequencing batch reactor with a working volume of 54 m3 was used to investigate nitrogen removal via nitrite from municipal wastewater at normal and low water temperature. The obtained results showed that high nitrogen removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(138 citation statements)
references
References 18 publications
9
122
2
5
Order By: Relevance
“…Moreover, most described AOB have an optimal temperature of around 28°C (36). On the other hand, some studies indicated that nitrite-oxidizing bacteria were capable of growing at lower temperatures ranging from Ϫ2°C (37) to 17°C (36) and that at 10°C to 15°C, NOB had a higher activity than AOB (15). If NOB had a competitive advantage over AOB or anammox bacteria below 20 to 25°C, depending on their affinity for nitrite and O 2 , they could take up the limiting O 2 and nitrite before AOB and anammox bacteria, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, most described AOB have an optimal temperature of around 28°C (36). On the other hand, some studies indicated that nitrite-oxidizing bacteria were capable of growing at lower temperatures ranging from Ϫ2°C (37) to 17°C (36) and that at 10°C to 15°C, NOB had a higher activity than AOB (15). If NOB had a competitive advantage over AOB or anammox bacteria below 20 to 25°C, depending on their affinity for nitrite and O 2 , they could take up the limiting O 2 and nitrite before AOB and anammox bacteria, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to lower specific activities and growth rates for both anammox bacteria and AOB. Indeed, it was reported that the activities of anammox bacteria and AOB both decreased at 15 to 20°C (13,14) and that partial nitrification was difficult to achieve in winter because of the varying temperature of municipal wastewater (15). Nevertheless, several studies showed that nitrogen removal at a lower temperature by an anammox process can work (14,16,17); still, in none of these studies was it possible to maintain a stable anammox-AOB culture (nitritation-anammox) at temperatures lower than 20°C.…”
mentioning
confidence: 99%
“…Although ammonia has been confirmed to be removed through SND, the organisms responsible for nitrification are still unknown. In the process of shortcut nitrogen removal, NOB could be gradually washed out from system due to the unfavorable environment like low DO [22]. From Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers argue that pH profile is the best indicator of the changes in the microbes profile occurring inside a SBR reactor [64]. However, the background alkalinity present in the wastewater often provides a strong buffering capacity that minimises noticeable variation in the pH.…”
Section: Process Control Strategiesmentioning
confidence: 99%